2020
DOI: 10.1002/ece3.5914
|View full text |Cite
|
Sign up to set email alerts
|

Gray plumage color is more cryptic than brown in snowy landscapes in a resident color polymorphic bird

Abstract: Camouflage may promote fitness of given phenotypes in different environments. The tawny owl (Strix aluco) is a color polymorphic species with a gray and brown morph resident in the Western Palearctic. A strong selection pressure against the brown morph during snowy and cold winters has been documented earlier, but the selection mechanisms remain unresolved. Here, we hypothesize that selection favors the gray morph because it is better camouflaged against predators and mobbers in snowy conditions compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 58 publications
5
33
0
2
Order By: Relevance
“…In order to achieve such information, we need empirical studies of natural populations where this variation can be monitored. Evidence is accumulating that colour polymorphism-a phenotypic marker for genetic polymorphism-is associated with morph-specificity in habitat use (Galeotti and Cesaris 1996;Dreiss et al 2011; Passarotto et al 2018;Koskenpato et al 2020) and differential fitness depending on environmental conditions (Karell et al 2011a;Emaresi et al 2014;San-José et al 2019). Such differences are expected to reflect variations in food resource use and diet specialisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve such information, we need empirical studies of natural populations where this variation can be monitored. Evidence is accumulating that colour polymorphism-a phenotypic marker for genetic polymorphism-is associated with morph-specificity in habitat use (Galeotti and Cesaris 1996;Dreiss et al 2011; Passarotto et al 2018;Koskenpato et al 2020) and differential fitness depending on environmental conditions (Karell et al 2011a;Emaresi et al 2014;San-José et al 2019). Such differences are expected to reflect variations in food resource use and diet specialisation.…”
Section: Discussionmentioning
confidence: 99%
“…These cyclic food conditions limit the reproduction of tawny owls in this environment as in low vole cycle phases tawny owls often skip breeding (Karell et al 2009a). In general, the grey tawny owls are more common in dry and cold areas (Galeotti and Cesaris 1996;PK et al unpublished data), and they are adapted to resist snow-rich and cold winters (Karell et al 2011a), presumably because they have lower energy requirements in extremely cold conditions (Piault et al 2009;Karell et al 2011a;Koskenpato et al 2016Koskenpato et al , 2020. In concordance with this, the life span of the grey morph is indeed longer than that of the brown morph at the Northern limit of the species range (Brommer et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely there are survival costs associated with the presence of snow on the ground, possibly due to phenotypic mismatch [38,39]. Interestingly, exposure to deep snow did not influence overall survival, but individuals that selected deep snow were more likely to survive the winter.…”
Section: (A) Personality and Behavioural Plasticity In Roost Site Selectionmentioning
confidence: 97%
“…For species that do not moult white in winter, even slight differences in coloration can influence the effectiveness of crypsis in snow, with consequences for overwinter survival. For example, brown morph tawny owls (Strix aluco) are more visible than grey morph individuals against a snowcovered landscape [38], and are less likely to survive during snowy winters [39]. For other winter-adapted species, such as ruffed grouse (Bonasa umbellus), which has brown plumage year-round, snow cover may result in phenotypic mismatch, exposing grouse to predators.…”
Section: Introductionmentioning
confidence: 99%
“…The grey morph is suggested to avoid predation better in snowy winter conditions and the brown (red) morph should do better in less snowy circumstances. This camouflage effect has been assessed in a citizen science study in which pictures of grey and brown Tawny Owls in various backgrounds were shown to human observers (Koskenpato et al 2020). It has been suggested that the recent increase of brown Tawny Owls in Finland (1961Finland ( -2008 is a consequence of warmer and less snowy winters due to climate warming (Karell et al 2011).…”
mentioning
confidence: 99%